ZONASI DAERAH RAWAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Jawad, Abdul; Nurdjali, Bachrun; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2015)
Kubu Raya district has common place of forest fire every dry season. Based from Unit Penanggulangan Hutan dan Lahan (UPKHL) of forestry of Ministry West Kalimantan Province data up to October 2013, there is 349 hotspots in Kabupaten Kubu Raya. Kubu Raya indeed susceptible of forest fires, it is cause by the terrain that dominated by peatlands that easily combusted. The purpose of this research is to identified and maping forest fire spot in Kubu Raya district based on parameter analysis of peat depth, elevation and land cover. Forest fire zone in Kubu Raya district identified using Geographic Information System application is done overlaying land cover data, elevation and peat depth wich has scoring. After analyzed, data suitable with danger level of spot/zone that base of combination divided into 5 level wich is save, low, medium, high and very high. The result of this analysis shown that Kubu Raya district area is 829,969.17 Ha, consist of 92,804,54 Ha (11.18%) very high, 349,681.47 Ha (42,13%) high zone, 339,352.39 Ha (40.8% ) medium zone, 38,271.98 Ha (4.61% ) low zone Â and 9,858.79 Ha (1.19%) save zone. Keywords: Hotspots, Geographic Information System.